INTRACRANIAL PRESSURE MONITORING - Retno Widiyanthi (E-Jurnal Medika Udayana, 2013)
Intracranial pressure is total of pressure that is produced by brain, blood, and cerebrospinal fluid/CSF in the tight cranial space. As a respon to intracranial pressure increasing, compensation begin by movement of CSF from ventricle to cerebral subarachnoidal space, and increase the absorption of CSF. Increasing of ICP usually caused by increasing of brain volume (cerebral oedem), blood (intracranial bleeding), space occupying lesion, or CSF (hidrocephalus). Indication in ICP monitoring can be seen from : neurological criteria, abnormal CT-scan result when admission, normal CT-scan result, but had more two risk factors. According to the procedure that must be done, there are two methods in ICP monitoring: invasive ICP monitoring methodes and non-invasive measuring method. Increasing of ICP will decrease the compliance of brain, pulsation of artery more clearly, and the component of vein is lost.